ULTRASTRUCTURAL LOCALIZATION OF CALCITONIN IN THE PARAFOLLICULAR CELLS OF PIG THYROID GLAND WITH CYTOCHROME c-LABELED ANTIBODY FRAGMENTS - De Grandi, P. B. (The Rockefeller University Press, 1971)
Parafollicular cells in mammalian thyroid glands are thought to be responsible for the secretion of calcitonin. In this study, calcitonin was localized in pig thyroid gland by an indirect immunocytochemical technique using rabbit antiserum directed against synthetic porcine calcitonin for the first step, and sheep Fab fragments prepared against rabbit Fab and coupled to cytochrome c for the second step. The antigenic determinants of calcitonin were present only in the parafollicular cells, whose secretory granules were heavily labeled. Labeling of the cytoplasmic matrix is thought to indicate a possible leakage of the polypeptide from the granules. A striking observation was the complete absence of labeling in the cisternae of the rough-surfaced endoplasmic reticulum and of the Golgi apparatus. It is concluded that the secretory granules of parafollicular cells contain calcitonin; the mechanism of synthesis of this peptide is not clearly understood.